Perceived attachment to God relates to body appreciation: mediating roles of self-compassion, sanctification of the body, and contingencies of self-worth - Kusina, Jessica R. (Mental health, religion & culture, 2021)
Various studies demonstrate links between attachment to God and body image, though few consider secure attachment to God or positive body image specifically. Further, little is known about explanatory mechanisms, and many studies have relied on samples of White college women. In the current study, we proposed several potential mediators to better understand the relationship between perceived attachment to God and body image. Emerging adults (N = 288) in the U.S. responded to multiple measures assessing body image and religion/spirituality through the Amazon Mechanical Turk Prime platform. Findings revealed that a more secure perceived attachment to God was associated with more body appreciation. Self-compassion, sanctification of the body, and certain contingencies of self-worth mediated these relationships, with patterns differing somewhat based on gender identity. These findings expand the literature pertaining to r/s and body image and can hopefully be utilized to help emerging adults cultivate positive images of their bodies.